Investigating pore to pore exchange in systems saturated with water and oil - Lewis, Rhiannon T.; Nåden, Susanne; Seland, John Georg (Diffusion Fundamentals, 2013)
Relaxation Exchange Spectroscopy (REXSY) has not previously been performed on samples containing different liquids. We present a pulse sequence that combines a Pulsed Gradient Spin Echo with REXSY, which we call PGSE-REXSY. Using this pulse sequence it is possible to separate the signals from two liquid components, here oil and water, simultaneously present within a sample due to the difference in diffusion properties. A REXSY analysis can then be performed on the individual liquids. The technique is very relevant to applications in petroleum research, and could potentially be used to determine how the mobility of one liquid is influenced by the presence of the other. We also show that compared to a two-dimensional Inverse Laplace Transform, a discrete multi-exponential component model is more robust when performing a quantitative analysis of REXSY data.